Histopathologic Findings of Patients With Biopsy‐Negative Giant Cell Arteritis Compared to Those Without Arteritis: A Population‐Based Study. Issue 6 (26th May 2016) - Muratore, Francesco; Cavazza, Alberto; Boiardi, Luigi; Lo Gullo, Alberto; Pipitone, Nicolò; Germanò, Giuseppe; Bisagni, Alessandra; Cimino, Luca; Salvarani, Carlo
Abstract : Objective: To evaluate whether there are histopathologic features of negative temporal artery biopsy (TAB) that allow differentiation between patients with giant cell arteritis (GCA) and those without. Methods: All consecutive patients with negative TAB seen between January 2009 and December 2012 were selected retrospectively. Demographic, clinical, and laboratory data at presentation and at each followup visit were collected. A pathologist with expertise in vasculitis and blinded to clinical data and final diagnosis reviewed all negative TABs. Histopathologic features evaluated were the presence of a focal mediointimal scar, medial attenuation, intimal hyperplasia, fragmentation of inner elastic lamina, calcification, adventitial fibrosis, and neoangiogenesis. Results: After a median (interquartile range [IQR]) followup period of, respectively, 19 months (9.2–31.2) and 26.3 months (4.9–36.7) ( P = 0.041), 38 (55%) of 69 patients had a final diagnosis of TAB‐negative GCA, while in the remaining 31 (45%) of 69 patients GCA was excluded. The American College of Rheumatology classification criteria for GCA were satisfied by 31 (81.6%) of 38 patients and 2 (6.5%) of 31 patients ( P < 0.0001). Compared to non‐GCA patients, those with TAB‐negative GCA had more frequent cranial manifestations and higher erythrocyte sedimentation rates and C‐reactive protein levels. The frequency of patients receiving prednisone, the mean dose, and the duration of prednisone treatment at TAB were similar in the 2 groups. There were no significant differences between TAB‐negative GCA and non‐GCA patients in the frequencies of all the histologic features evaluated. Conclusion: The histologic features of negative TABs evaluated in this study do not allow for the differentiation between GCA and non‐GCA patients. In the absence of an inflammatory infiltrate, other histologic changes of the temporal artery wall are not specific for GCA.